(untitled) (Conferencea, 2023)
The main image of the poem is the lyrical hero, that is, the lyrical subject, whose inner experiences and feelings are revealed and manifested in a life situation. If the poem includes a character as well as a lyrical hero, it is a lyric with a character. "In order to belong to a lyric with a character, another person should become one of the subjects of the poem, the lyrical experience (thought, feeling) expressed in his language should acquire an independent ideological and artistic value, and the poem should acquire a dialogic (polyphonic) feature" [2, 254-p]. The possibilities of the poet expand in the character lyric. His thoughts are reflected in the feelings of the lyrical hero, the character’s attitude to reality. The character entering the work completes the lyrical hero. Among the works related to character lyrics, we can include the work of several other poets such as Erkin Vahidov ("Today’s Youth"), Khurshid Davron ("The Beautiful World", "Babur", "Unhappiness", "Kaygu").